1993
DOI: 10.1073/pnas.90.23.10937
|View full text |Cite
|
Sign up to set email alerts
|

Cytokinin stimulates dihydropyridine-sensitive calcium uptake in moss protoplasts.

Abstract: Ca2 influx through dihydropyridine (DHP)-sensitive Ca2+ channels is thought to be an early event in cytokinin-induced bud formation in moss protonema because DHP antagonists inhibit bud formation in the presence of cytokinin and DHP agonists stimulate bud formation in the absence of cytokinin [Conrad, P. A. & Hepler, P. K. (1988) Plant Physiol. 86, 684-687]. In the present study, we established the presence of a DHP-sensitive Ca2+ transport system by measuring 4-Ca2+ influx into moss protoplasts. Ca2+ influx … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
30
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 36 publications
4
30
1
Order By: Relevance
“…Similar results were observed with nifedipine, which blocks animal and plant L-type calcium channels (Schroeder and Thuleau 1991;Schumaker and Gizinski 1993). At a concentration of 60 | XM it could totally inhibit the light induction of cab and fnr, whereas chs induction was again superinduced (Fig.…”
Section: Identification Of Inhibitors That Block Calciumdependent Gensupporting
confidence: 73%
“…Similar results were observed with nifedipine, which blocks animal and plant L-type calcium channels (Schroeder and Thuleau 1991;Schumaker and Gizinski 1993). At a concentration of 60 | XM it could totally inhibit the light induction of cab and fnr, whereas chs induction was again superinduced (Fig.…”
Section: Identification Of Inhibitors That Block Calciumdependent Gensupporting
confidence: 73%
“…It has been shown that verapamil at micromolar concentrations inhibited voltage-dependent Ca and Cd influx in animal cells (Hinkle et al, 1987), but the effects reported in plant studies seem inconsistent (Pineros and Tester, 1997): Ca influx into protoplasts from Physcomitrella patens (Schumaker and Gizinski, 1993), carrot (Daucus carota; Graziana et al, 1988), Amaranthus tricolor (Rengel and Elliot, 1992), and tobacco (Nicotiana tabacum; Volotovski et al, 1998) and into plasma membrane vesicles isolated from oat (Avena sativa) roots (Gonzalez et al, 1999) was reduced upon exposure to verapamil, although up to 100 m verapamil did not block the calcium influx into plasma membrane vesicles isolated from wheat roots or oat seedlings (Huang et al, 1994;Babourina et al, 2000). Furthermore, in aquatic plants, it was found to inhibit Ca uptake but to increase Cd uptake (Karez et al, 1990;Tripathi et al, 1995).…”
Section: Effects Of Cold and Competitors On CD And Zn Uptakementioning
confidence: 99%
“…While There is strong evidence for three calcium antagonist receptor sites on the L-type voltage-dependent calcium channels in animal cells: one for DHPs, one for phenylalkylamines, and one for benzothiazepines (42). We investigated the ability of these molecules to compete for [ ]azidopine binding in a manner qualitatively similar to their ability to inhibit calcium influx into moss protoplasts (21). Inhibition is most likely due to a direct competition for the azidopine-binding site by the DHPs and due to an allosteric inhibition of azidopine binding by verapamil and diltiazem (30 -33).…”
Section: Specific Binding Of [mentioning
confidence: 99%
“…We have previously characterized calcium influx into isolated moss protoplasts and have established that the transport activity of the moss calcium channel shares common characteristics with L-type calcium channels in animal cells. Calcium transport in moss is voltagedependent, stimulated by DHP agonists, and inhibited by DHP antagonists, phenylalkylamines, and benzothiazepines (21). A novel feature of the transport activity of this channel is hormonal modulation by cytokinin (21).…”
mentioning
confidence: 99%
See 1 more Smart Citation